System dynamics for sequencing batch reactors modeling - Canales, Fausto Alfredo; Mendes, Carlos André Bulhões (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Wastewater treatment by sequencing batch reactors is a variation of the activated-sludge process, because they combine all of the treatment steps and processes into a single tank. This paper presents a model created in Vensim and based on system dynamics with the aim of simu- lating the filling and depletion of the tanks in a wastewater treatment system by sequencing batch reactors, considering a high variability of the inflow along the day. The system shown is comprised of two tanks, a bypass, and an optional influent equalization basin. Some examples are included to illustrate the capacity of the model to simulate different system configurations, something that is supported by the results of these examples. The model can be adapted to include characteristics of similar wastewater treatment systems, allowing the evaluation of different conditions depending on the characteristics of wastewater inflows and physical or chemical features of the treatment plant.